Specialized pediatric palliative care services for children dying from cancer: A repeated cohort study on the developments of symptom management and quality of care over a 10-year period. (March 2019) - Zernikow, Boris; Szybalski, Katharina; Hübner-Möhler, Bettina; Wager, Julia; Paulussen, Michael; Lassay, Lisa; Jorch, Norbert; Weber, Carola; Schneider, Dominik T; Janßen, Gisela; Oommen, Prasad T; Kuhlen, Michaela; et al.
Background: About one quarter of children affected with cancer die. For children and their families, the end-of-life period is highly distressing. Aim: This study focused on how end-of-life care in pediatric cancer patients changed over a period of 10 years and if changes in pediatric palliative care structures were associated with quality of care. Design: Over a 10-year period, all pediatric oncology departments in one German federal state were invited to participate in a repeated cross-sectional cohort study at three time-points (2005, 2010, 2015). Departments invited parents whose children died due to cancer 5 years earlier to participate. Identical semi-structured interviews were conducted with each cohort by the Survey of Caring for Children with Cancer. In addition, departments provided information on their pediatric palliative care infrastructure. Participants: In total, 124 families participated; 73% of interviews were conducted with mothers, 18% with fathers, and 9% with both parents. Results: Parents' perception of symptom occurrence, symptom burden, and effectiveness of symptom-related treatment remained stable over the 10-year period. Over time, the availability of pediatric palliative care ( p < 0.001) as well as quality and satisfaction ratings of care ( p < 0.001) increased significantly. A growing number of children received specialized pediatric palliative care at home during the end-of-life period ( p = 0.009). Along with this development, more families had the chance to plan the location of death ( p = 0.003), and more children died at the preferred location ( p = 0.001). Conclusion: Advances in the availability of pediatric palliative care were associated with improvement in some aspects of quality of care (e.g. location of death) while other aspects, such as effectiveness of symptom management, remained unchanged. Further research is required to determine whether additional improvement in structural quality may increase the effectiveness of symptom management.